Metagenomic next-generation sequencing-based diagnosis of Pneumocystis jirovecii pneumonia in patients without human immunodeficiency virus infection: A dual-center retrospective propensity matched study - Jin-zhu Wang; Jiang-bo Wang; Ding Yuan; Chang-hua Sun; Lin-lin Hou; Yan Zhang; Xiang-hong Yang; Hong-xiang Xie; Yan-xia Gao (Journal of Infection and Public Health, 2025)
Background: Pneumocystis jirovecii pneumonia (PJP), caused by Pneumocystis jirovecii (PJ), is an opportunistic infection prevalent in clinical settings. However, large-scale studies on the efficacy of metagenomic next-generation sequencing (mNGS)-based diagnosis of PJP in patients without human immunodeficiency virus infection (HIV) are lacking. Methods: The study included 168 patients diagnosed with either PJP (84) or other pneumonia types (non-PJP patients; 84) who underwent mNGS-mediated bronchoalveolar lavage fluid (BALF) analysis, Gomori methenamine silver (GMS) staining and peripheral blood 1,3-beta-D-glucan (BDG) testing. Additionally, patients with PJP were categorized into survival (n = 55) and non-survival (n = 29) groups based on a 28-day in-hospital outcome to compare clinical characteristics, inflammatory markers, PJ sequence counts in BALF, and serum BDG levels. Results: Serum BDG levels, the proportion of patients with serum BDG of > 60 pg/mL and > 200 pg/mL were notably higher in the PJP group compared with that in the non-PJP group (all P< 0.05). The sensitivity and specificity of mNGS in diagnosing PJP were higher than those of serum BDG testing (sensitivity: 100 % vs. 63.0 %; specificity: 96.4 % vs. 90.4 %; both P< 0.05). The most common coinfection was viral (30.9 %), followed by bacterial–viral coinfections (13.0 %). Treatment regimens were altered for 83.3 % of patients based on the mNGS results. The patients in the non-survival group showed markedly higher serum BDG levels (142.5 [32.7, 277.7] vs. 123.0 [34.0, 164.0]) and a higher proportion of PJ sequence counts of > 1 × 105 (13.7 % vs. 0, P= 0.005) relative to those in the survival group. Conclusion: The mNGS showed superior performance over serum BDG testing and GMS staining in diagnosing PJP in non-HIV patients and identified a broader range of coinfections.